Analisis Kinerja Penjualan Menggunakan Business Intelligence Berbasis KPI (Studi Kasus: Yarage Coffee House) - Wilda Aprilia Mustika Sari; Bagja Nugraha; Ahmad Khusaeri (Jurnal Informatika dan Teknik Elektro Terapan, 2026)
Yarage Coffee House has implemented a Point of Sale (POS) system to record sales transactions; however, the generated data has not been optimally utilized as an information source to support analysis and business decision-making. Sales data is still presented in the form of simple reports, making it difficult to monitor overall sales performance. This study aims to analyze sales performance using a Business Intelligence approach based on Key Performance Indicators (KPI) with supporting Pareto ABC analysis. The research was conducted through the stages of data collection, KPI Modeling, Extract, Transform, Load (ETL) process, data analysis, and result interpretation. KPI determination was based on information needs obtained through interviews and validated using the SMART method. The results show that the implementation of KPI-based Business Intelligence was able to transform transaction data into more structured and informative information presented through an interactive dashboard using Tableau. The analysis results indicate total revenue of IDR 38,770,000 with a total of 1,238 transactions. Pareto ABC analysis shows that Category A contributed a cumulative 77% of total revenue, thereby supporting more effective and data-driven business decision-making.